On the cyclic stability diagram of offshore wind turbine supported on multiple foundations in saturated dense sand. (February 2023) - Nielsen, Kent; Svenningsen, Jacob; Barari, Amin; Farahani, Sina; Ibsen, Lars Bo
Highlights: This paper presents a predictive model describing the accumulated rotation of a tripod structure. A simple but robust cyclic load response diagram was established in order to provide an insight into stable modes of cyclic loading. The FEM model is validated against previously published centrifuge test results. Using modified least-squares method, a generalized expression for the estimation of induced rotation of OWTs was proposed. The dynamic FE analysis enabled the identification of the ''self-healing'' phenomenon due to enhanced stiffness degradation of a foundation in tension. Abstract: This study explored the issue of cyclic loading on a tripod suction bucket foundation system in silty sand through three-dimensional (3D) finite element (FE) models by developing a cyclic stability diagram, in which the response is presented in terms of the average load ratio (ALR) and the cyclic load ratio (CLR), and three regions are identified: (1) no cyclic load effects, (2) cyclic load effects, and (3) severe load effects after approximately 1000 one-way load cycles. The simulations, based on dynamic FE analysis, enabled the identification of the ''self-healing'' phenomenon due to enhanced stiffness degradation of a foundation in tension by incorporating the correct estimate of the soil-foundation interface and geometric nonlinearities. In addition, an approximating expression for the calculation of the accumulated rotation of offshore wind turbine (OWT) supported on multiple foundations is provided as a function of ALR and CLR utilizing modified least-squares method (MLSM). The proposed expression leads to notable improvements in the prediction of induced rotation of OWTs such that the coefficient of determination, R 2, was obtained ranging from minimum value of 0.89 to a maximum value of 0.99. This study suggests that the salient features of multiple foundations must be considered in the design process of offshore wind turbines.